PENGARUH MANAJEMEN PENGETAHUAN DAN BUDAYA PERUSAHAAN TERHADAP KINERJA PERUSAHAN (SURVEY PADA INDUSTRI KECIL DAN MENENGAH DI PROVINSI JAMBI) - Susi Desmaryani (Universitas Batanghari Jambi, 2014)
This research was on the small and medium Industries in Province Jambi, Sumatera, which had an objective to test the ability of small and medium Industries to achieve the good performance in the influence of knowledge management and corporate culture . Types of metholodology used in this research were descriptive and verification. Techniques of data collection were the study of literature, observation, interview and questionary with the sample of 110 companies. The sampling technique was proportional stratified random sampling and processed by using Structural Equation Modeling (SEM) to produce a causal relationship between the variables.The results of descriptive analysis indicated that knowledge management in the category of “ rather good”, “rather strong” category for corporate culture, and “ rather good” category for corporate performance. Verificative analysis showed that : (1) knowledge management and corporate culture significantly positive effected the company performance.Keywords : Knowledge Management, Corporate Culture, and Company Performance